Molecular sieve SSZ-123, its synthesis and uses
Patent Information
- Application Number
- JP2023513464
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-28
- Filing Date
- 2021-05-10
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2041-05-10
Smart Images

Figure 0007645364000008 
Figure 0007645364000009 
Figure 0007645364000001
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to and the benefit of U.S. Provisional Application No. 63 / 071,451, filed August 28, 2020.
[0002] Field This disclosure relates to a novel synthetic crystalline molecular sieve of the MFS framework type, designated SSZ-123, its synthesis, and its use in organic compound conversion and sorption processes. [Background technology]
[0003] background Molecular sieves are a commercially important class of materials having a well-defined crystal structure with a defined pore structure as revealed by distinct X-ray diffraction (XRD) patterns, and having specific chemical compositions. The crystal structure defines the cavities and pores that are characteristic of particular types of molecular sieves.
[0004] Molecular sieves are classified by the Structure Commission of the International Zeolite Association according to the rules of the IUPAC Commission on Zeolite Nomenclature. According to this classification, framework zeolites and other crystalline microporous molecular sieves have unique structures and are assigned unique three-letter codes. These are described, for example, in "Atlas of Zeolite Framework Types" by Ch. Baerlocher, LB McCusker and DH Olson (Elsevier, Sixth Revised Edition, 2007).
[0005] ZSM-57 is a molecular sieve material that has a unique two-dimensional pore system consisting of 10 intersecting ring channels and 8 intersecting ring channels. The framework structure of ZSM-57 has been assigned the three-letter code MFS by the Structure Commission of the International Zeolite Association.
[0006] The composition and characteristic X-ray diffraction pattern of ZSM-57 are disclosed in U.S. Pat. No. 4,873,067, which also describes the conventional synthesis of the molecular sieve in the presence of a structure directing agent comprising N,N,N,N',N',N'-hexaethylpentanediammonium (HEPD) cation.
[0007] SH. Lee et al. (J. Catal. 2000, 196, 158-166) reported that crystallization of ZSM-57 in the presence of HEPD was possible only from synthesis mixtures within a very narrow compositional range: synthesis mixtures with SiO2 / Al2O3 molar ratios below 40 produced materials other than ZSM-57.
[0008] According to the present disclosure, an aluminum-rich molecular sieve of the MFS framework type, designated SSZ-123, has now been synthesized using the 1-ethyl-1-[5-(triethylammonio)pentyl]piperidinium cation as a structure directing agent. Summary of the Invention
[0009] summary In a first embodiment, there is provided an MFS framework type molecular sieve having a SiO2 / Al2O3 molar ratio in the range of 10-35.
[0010] In a second embodiment, an MFS framework-type aluminosilicate molecular sieve is provided which, in its as-synthesized form, contains 1-ethyl-1-[5-(triethylammonio)pentyl]piperidinium cations in its pores.
[0011] In a third aspect, a method for synthesizing an MFS framework-type molecular sieve is provided, the method comprising: (1) preparing a reaction mixture comprising (a) a silicon source, (b) an aluminum source, (c) an alkali or alkaline earth metal (M) source, (d) a structure directing agent comprising 1-ethyl-1-[5-(triethylammonio)pentyl]piperidinium cation (Q), (e) a hydroxide ion source, and (f) water; and (2) subjecting the reaction mixture to crystallization conditions sufficient to form molecular sieve crystals.
[0012] In a fourth aspect, there is provided a process for converting a feedstock comprising organic compounds to conversion products, the process comprising contacting the feedstock under organic compound conversion conditions with a catalyst comprising an MFS framework type molecular sieve, wherein the molecular sieve has a molar ratio of SiO2 / Al2O3 in the range of 10-35. In relation to the present invention, the following is further disclosed: [1] SiO in the range of 10-35 2 / Al 2 O 3 A molecular sieve of MFS framework type having a molar ratio of [2] SiO 2 / Al 2 O 3 The molecular sieve according to [1], wherein the molar ratio is in the range of 15 to 30. [3] A molecular sieve of MFS framework type that, in its as-synthesized form, contains 1-ethyl-1-[5-(triethylammonio)pentyl]piperidinium cations in its pores. [4] SiO in the range of 10~35 2 / Al 2 O 3 The molecular sieve according to [3], having a molar ratio of [5] SiO in the range of 15-30 2 / Al 2 O 3 The molecular sieve according to [3], having a molar ratio of [6] A method for synthesizing an MFS framework molecular sieve comprising the steps of: (1) (a) a silicon source; (b) a source of aluminum; (c) a source of an alkali or alkaline earth metal (M); (d) a structure directing agent comprising a 1-ethyl-1-[5-(triethylammonio)pentyl]piperidinium cation (Q); (e) a hydroxide ion source, and (f) preparing a reaction mixture comprising: (2) subjecting said reaction mixture to crystallization conditions sufficient to form crystals of said molecular sieve. [7] The method according to [6], wherein the reaction mixture has the following composition, in terms of molar ratio: [Table 1A] [8] The method according to [6], wherein the reaction mixture has the following composition, in terms of molar ratio: [Table 1B] [9] The method of claim 6, wherein the silicon source is selected from colloidal silica, precipitated silica, fumed silica, alkali metal silicates, tetraalkyl orthosilicates, and any combination thereof.
[10] The method of claim 6, wherein the aluminum source is selected from alumina hydrate, aluminum hydroxide, alkali metal aluminate, aluminum alkoxide, water-soluble aluminum salt, and any combination thereof.
[11] The method according to [6], wherein the alkali or alkaline earth metal (M) comprises potassium.
[12] The method of claim 6, wherein crystallization conditions include heating the reaction mixture under autogenous pressure at a temperature between 120° C. and 200° C. for a time period between 1 day and 21 days.
[13] A process for converting a feedstock containing organic compounds to conversion products, the process comprising contacting the feedstock under organic compound conversion conditions with a catalyst comprising a molecular sieve of MFS framework type, wherein the molecular sieve has an SiO 2 content in the range of 10-35. 2 / Al 2 O 3 The process having a molar ratio of [Brief description of the drawings]
[0013] Brief description of the drawings [Figure 1] 1 shows a scanning electron microscope (SEM) image of the product of Example 1.
[0014] [Diagram 2] 1 shows a powder X-ray diffraction (XRD) pattern of the product of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Detailed Description definition The term "framework type" as used herein has the meaning set forth in "Atlas of Zeolite Framework Types" Ch. Baerlocher, LB McCusker and DH Olson (Elsevier, Sixth Revised Edition, 2007).
[0016] The term "as-synthesized" is used herein to refer to the molecular sieve in the form after crystallization and prior to removal of the structure directing agent.
[0017] The term "anhydrous" is used herein to refer to a molecular sieve that is substantially free of both physically and chemically adsorbed water.
[0018] Molecular sieve synthesis The molecular sieve SSZ-123 can be synthesized by (1) preparing a reaction mixture comprising (a) a silicon source, (b) an aluminum source, (c) an alkali or alkaline earth metal (M) source, (d) a structure directing agent comprising 1-ethyl-1-[5-(triethylammonio)pentyl]piperidinium cation, (e) a hydroxide ion source, and (f) water; and (2) subjecting the reaction mixture to crystallization conditions sufficient to form crystals of the molecular sieve.
[0019] The reaction mixture may have a composition, in terms of molar ratios, within the ranges shown in Table 1. [Table 1]
[0020] Suitable sources of silicon include colloidal silica, precipitated silica, fumed silica, alkali metal silicates, and tetraalkyl orthosilicates (eg, tetraethyl orthosilicate).
[0021] Suitable sources of aluminum include alumina hydrate, aluminum hydroxide, alkali metal aluminates, aluminum alkoxides, and water-soluble aluminum salts (eg, aluminum nitrate).
[0022] The alkali or alkaline earth metal (M) is typically introduced into the reaction mixture along with a source of hydroxide ions. Examples of such metals include sodium and / or potassium, as well as lithium, rubidium, cesium, magnesium, and calcium. As used herein, the phrase "alkali or alkaline earth metal" does not mean that alkali metals and alkaline earth metals are used interchangeably, but instead means that one or more alkali metals can be used alone or in combination with one or more alkaline earth metals, and one or more alkaline earth metals can be used alone or in combination with one or more alkali metals.
[0023] The structure directing agent used in the preparation of SSZ-123 comprises a 1-ethyl-1-[5-(triethylammonio)pentyl]piperidinium cation (Q) represented by the following structure (1): [ka]
[0024] Suitable sources of Q are the hydroxide, chloride, bromide, and / or other salts of diquaternary ammonium compounds.
[0025] The reaction mixture may also contain seeds of crystalline material, such as MFS framework molecular sieves from a previous synthesis, desirably in an amount of 0.01 to 10,000 ppm (e.g., 100 to 5000 ppm) based on the weight of the reaction mixture. The seeds may be advantageous to improve the selectivity of SSZ-123 and / or shorten the crystallization process.
[0026] It should be noted that the reaction mixture components may be supplied from multiple sources, or two or more reaction components may be provided by a single source. The reaction mixture may be prepared in either a batch or continuous manner.
[0027] Crystallization and post-synthesis treatment Crystallization of the molecular sieves from the reaction mixture described above can be carried out under either static, tumbling or stirred conditions in a suitable reaction vessel such as a polypropylene jar or Teflon-lined or stainless steel autoclave at a temperature between 120° C. and 200° C. (e.g., 140° C. to 180° C.) for a time sufficient for crystallization to occur at the temperature used (e.g., 1 day to 21 days, or 3 days to 14 days). Crystallization is typically carried out in an autoclave such that the reaction mixture is under autogenous pressure.
[0028] Once the desired molecular sieve crystals are formed, the solid product is separated from the reaction mixture by standard separation techniques such as filtration or centrifugation. The recovered crystals are water washed and dried for a few seconds to a few minutes (e.g., 5 seconds to 10 minutes for flash drying) or for a few hours (e.g., 4 hours to 24 hours for oven drying at 75°C to 150°C) to obtain as-synthesized SSZ-123 crystals having at least a portion of the organic cations within their pores. The drying step can be carried out at atmospheric pressure or under vacuum.
[0029] The as-synthesized molecular sieve may be subjected to heat treatment, ozone treatment, or other treatment to remove some or all of the structure directing agent used in its synthesis. Removal of the structure directing agent may be accomplished by heat treatment (i.e., calcination) in which the as-synthesized molecular sieve is heated in air or in an inert gas at a temperature sufficient to remove some or all of the structure directing agent. Pressures less than atmospheric pressure may be used for heat treatment, but atmospheric pressure is preferred for convenience. Heat treatment may be performed at a temperature of at least 370° C. for at least 1 minute, typically for up to 20 hours (e.g., 1 to 12 hours). Heat treatment may be performed at a temperature of 925° C. or less. For example, heat treatment may be performed in air at a temperature of 400° C. to 600° C. for about 1 hour to 8 hours.
[0030] Any extraframework metal cations in the molecular sieve can be replaced with hydrogen, ammonium, or any desired metal cation according to techniques well known in the art (eg, by ion exchange).
[0031] Molecular sieve characterization The as-synthesized anhydrous form of the molecular sieve SSZ-123 may have a chemical composition, in molar ratios, within the ranges shown in Table 2. [Table 2]
[0032] In calcined form, the molecular sieve SSZ-123 can have a chemical composition including the following molar relationships: Al2O3:(n)SiO2 (wherein n is in the range of 10 to 35 (e.g., 10 to 33, 10 to 30, 15 to 35, 15 to 33, or 15 to 35)).
[0033] Powder XRD patterns indicative of MFS framework-type molecular sieves can be found in “Collection of Simulated XRD Powder Patterns for Zeolites” MMJ Treacy and JB Higgins (Elsevier, Fifth Revised Edition, 2007).
[0034] The powder XRD patterns presented herein were collected by standard techniques. Slight variations in the diffraction pattern may be due to variations in the molar ratio of framework species in a particular sample due to changes in lattice constants. Furthermore, sufficiently small crystals affect the shape and intensity of the peaks, resulting in significant peak broadening. Slight variations in the diffraction pattern may also be due to variations in the organic compounds used in the preparation. Calcination may result in slight shifts in the XRD pattern. Despite these slight perturbations, the basic crystal lattice structure remains unchanged.
[0035] Industrial Applicability Molecular sieve SSZ-123 (with some or all of the structure directing agent removed) can be used as an adsorbent or as a catalyst to catalyze a wide variety of organic compound conversion processes, including many of current commercial / industrial importance. Examples of chemical conversion processes that are effectively catalyzed by SSZ-123, alone or in combination with one or more other catalytically active substances, such as other crystalline catalysts, include processes that require catalysts with acid activity. Examples of organic conversion processes that can be catalyzed by SSZ-123 include cracking, hydrocracking, disproportionation, alkylation, oligomerization, and isomerization.
[0036] As with many catalysts, it may be desirable to combine SSZ-123 with another material that is resistant to the temperatures and other conditions used in organic conversion processes. Such materials include active and inactive materials, and synthetic or natural zeolites, as well as inorganic materials, such as clays, silica, and / or metal oxides, such as alumina. The metal oxides may be naturally occurring or in the form of gelatinous precipitates or gels, such as mixtures of silica and metal oxides. The use of materials together with the active SSZ-123 (i.e., combined with or present during the synthesis of a new material) tends to alter the conversion and / or selectivity of the catalyst in a particular organic conversion process. Inactive materials suitably function as diluents to control the amount of conversion in a given process so that products can be obtained in an economical and orderly manner without the use of other means to control the reaction rate. These materials may be incorporated into natural clays (e.g., bentonite and kaolin) to improve the crush strength of the catalyst under commercial operating conditions. These materials (i.e., clays, oxides, etc.) function as binders for the catalyst. In commercial use, it is desirable to provide a catalyst with good crush strength, since it is desirable to prevent the catalyst from breaking down into powdery materials. These clay and / or oxide binders have typically been used only to improve the crush strength of the catalyst.
[0037] Natural clays that can be hybridized with SSZ-123 include the montmorillonite and kaolin families, including the sub-bentonites, commonly known as Dixie, McNamee, Georgia, and Florida clays, in which the major mineral components are halloysite, kaolinite, dickite, nacrite, or anaxite. Such clays can be used in the raw state as originally mined, or first subjected to calcination, acid treatment, or chemical modification. Binders useful for hybridization with SSZ-123 also include inorganic oxides, such as silica, zirconia, titania, magnesia, beryllia, alumina, and mixtures thereof.
[0038] In addition to the materials mentioned above, SSZ-123 may be composited with porous matrix materials such as silica-alumina, silica-magnesia, silica-zirconia, silica-thoria, silica-beryllia, silica-titania, and the ternary configurations, silica-alumina-thoria, silica-alumina-zirconia, silica-alumina-magnesia, and silica-magnesia-zirconia.
[0039] The relative proportions of SSZ-123 and inorganic oxide matrix can vary widely, with the SSZ-123 content ranging from 1 to 90% (eg, 2 to 80% by weight) of the composite material. example
[0040] The following illustrative examples are intended to be non-limiting.
[0041] Example 1 2.45 g of deionized water, 0.37 g of 45% KOH solution, 2.68 g of 17.8% 1-ethyl-1-[5-(triethylammonio)pentyl]piperidinium hydroxide solution, 0.08 g of 50% Reheis F-2000 aluminum hydroxide dry gel, and 2.00 g of LUDOX® AS-30 colloidal silica (30 wt.% suspension / water) were mixed together in a Teflon® liner. The resulting gel was stirred until homogeneous. The liner was then capped and placed in a Parr Steel autoclave reactor. The autoclave was then placed in an oven heated to 160° C. for 12 days while tumbling at 43 rpm. The solid product was collected from the cooled reactor by centrifugation, washed with deionized water, and dried at 95° C.
[0042] The resulting product was analyzed by SEM and powder XRD. The SEM image is shown in Figure 1 and shows uniform fields of crystallinity. The powder XRD pattern of the as-synthesized material is shown in Figure 2, which is consistent with the material having an MFS framework type structure.
[0043] The SiO2 / Al2O3 molar ratio of the product was 18.8 as determined by inductively coupled plasma-atomic emission spectroscopy (ICP-AES) elemental analysis.
[0044] Example 2 1.84 g of deionized water, 0.28 g of 45% KOH solution, 2.01 g of 17.8% 1-ethyl-1-[5-(triethylammonio)pentyl]piperidinium hydroxide solution, 0.05 g of Reheis F-2000 aluminum hydroxide dry gel, and 1.50 g of LUDOX® AS-30 colloidal silica were mixed together in a Teflon® liner. The gel was stirred until homogeneous. The liner was then capped and placed in a Parr Steel autoclave reactor. The autoclave was then placed in an oven heated to 160° C. for 10 days while tumbling at 43 rpm. The solid product was collected from the cooled reactor by centrifugation, washed with deionized water, and dried at 95° C.
[0045] Powder XRD analysis showed the product to be an MFS framework molecular sieve.
[0046] The product had a SiO2 / Al2O3 molar ratio of 21.7 as determined by ICP-AES elemental analysis.
[0047] Example 3 2.46 g of deionized water, 0.37 g of 45% KOH solution, 2.68 g of 17.8% 1-ethyl-1-[5-(triethylammonio)pentyl]piperidinium hydroxide solution, 0.05 g of Reheis F-2000 aluminum hydroxide dry gel, and 2.00 g of LUDOX® AS-30 colloidal silica were mixed together in a Teflon® liner. The gel was stirred until homogeneous. The liner was then capped and placed in a Parr Steel autoclave reactor. The autoclave was then placed in an oven heated to 160° C. for 10 days while tumbling at 43 rpm. The solid product was collected from the cooled reactor by centrifugation, washed with deionized water, and dried at 95° C.
[0048] Powder XRD analysis showed the product to be an MFS framework molecular sieve.
[0049] The product had a SiO2 / Al2O3 molar ratio of 31.2 as determined by ICP-AES elemental analysis.
[0050] Example 4 3.20 g of deionized water, 0.37 g of 45% KOH solution, 1.79 g of 17.8% 1-ethyl-1-[5-(triethylammonio)pentyl]piperidinium hydroxide solution, 0.04 g of Reheis F-2000 aluminum hydroxide dry gel, and 2.00 g of LUDOX® AS-30 colloidal silica were mixed together in a Teflon® liner. The gel was stirred until homogeneous. The liner was then capped and placed in a Parr Steel autoclave reactor. The autoclave was then placed in an oven heated to 160° C. for 10 days while tumbling at 43 rpm. The solid product was collected from the cooled reactor by centrifugation, washed with deionized water, and dried at 95° C.
[0051] Powder XRD analysis showed the product to be a mixture of MFS-type molecular sieves and a dense phase.
[0052] Example 5 2.44 g of deionized water, 0.37 g of 45% KOH solution, 2.68 g of 17.8% 1-ethyl-1-[5-(triethylammonio)pentyl]piperidinium hydroxide solution, 0.10 g of Reheis F-2000 aluminum hydroxide dry gel, and 2.00 g of LUDOX® AS-30 colloidal silica were mixed together in a Teflon® liner. The resulting gel was stirred until homogeneous. The liner was then capped and placed in a Parr Steel autoclave reactor. The autoclave was then placed in an oven heated to 160° C. for 10 days while tumbling at 43 rpm. The solid product was collected from the cooled reactor by centrifugation, washed with deionized water, and dried at 95° C.
[0053] Powder XRD analysis showed the product to be a mixture of MFS framework type molecular sieves and an unknown phase.
[0054] Example 6 Example 5 was repeated, except that 5 wt % of as-synthesized MFS seed crystals prepared in Example 1 were added to the reaction mixture and the reaction time was reduced to 7 days.
[0055] Powder XRD analysis showed the product to be a phase-pure MFS framework molecular sieve.
[0056] The product had a SiO2 / Al2O3 molar ratio of 16.5 as determined by ICP-AES elemental analysis.
[0057] Example 7 The as-synthesized molecular sieve product from Example 1 was calcined in a muffle furnace under air flow at a temperature of about 540° C. for about 5 hours. After cooling, the sample was analyzed by powder XRD, which showed that the material was stable after calcination to remove the structure directing agent.
[0058] Example 8 The calcined material of Example 7 was treated with 10 mL (per gram of molecular sieve) of 1N ammonium nitrate solution at 95°C for 2 hours. The solution was cooled, decanted, and the same process was repeated. The dried product (NH4-SSZ-123) was subjected to micropore volume analysis by BET method using N2 as adsorbate. The molecular sieve had a pore size of 0.14 cm 3 / g micropore volume.
Claims
1. An aluminosilicate molecular sieve of MFS framework type which, in its as-synthesized form, contains 1-ethyl-1-[5-(triethylammonio)pentyl]piperidinium cations in its pores.
2. SiO in the range of 10 to 35 2 / Al 2 O 3 2. The molecular sieve of claim 1 having a molar ratio of:
3. SiO in the range of 15 to 30 2 / Al 2 O 3 2. The molecular sieve of claim 1 having a molar ratio of:
4. 1. A method for synthesizing an MFS framework molecular sieve, comprising: (1) (a) a silicon source; (b) a source of aluminum; (c) a source of alkali or alkaline earth metal (M); (d) a structure directing agent comprising a 1-ethyl-1-[5-(triethylammonio)pentyl]piperidinium cation (Q); (e) a hydroxide ion source, and (f) preparing a reaction mixture comprising water; (2) subjecting said reaction mixture to crystallization conditions sufficient to form crystals of said molecular sieve.
5. 5. The method of claim 4, wherein the reaction mixture has the following composition, in terms of molar ratios: 【Table 1A】
6. 6. The method of claim 5, wherein the reaction mixture has the following composition, in terms of molar ratios: 【Table 1B】
7. 5. The method of claim 4, wherein the silicon source is selected from colloidal silica, precipitated silica, fumed silica, alkali metal silicates, tetraalkyl orthosilicates, and any combination thereof.
8. 5. The method of claim 4, wherein the aluminum source is selected from alumina hydrate, aluminum hydroxide, alkali metal aluminates, aluminum alkoxides, water-soluble aluminum salts, and any combination thereof.
9. 5. The method of claim 4, wherein the alkali or alkaline earth metal (M) comprises potassium.
10. 5. The method of claim 4, wherein the crystallization conditions comprise heating the reaction mixture under autogenous pressure at a temperature between 120° C. and 200° C. for a time period between 1 day and 21 days.
11. The method of claim 4, wherein the as-synthesized molecular sieve is subjected to heat treatment, ozone treatment, or other treatment to remove some or all of the structure directing agent.
Citation Information
Patent Citations
Zeolite, synthesis and organic conversion reaction
JP1986072618A
Molecular sieve, cok-5, its synthesis and use
JP2016519646A
Manufacturing method of molecular sieves
JP2016523221A